PENGEMBANGAN DAYA SAING UMKM DI MALAYSIA DAN SINGAPURA: SEBUAH KOMPARASI - Abdul Mongid; FX Soegeng Notodihardjo (Jurnal Keuangan dan Perbankan, 2011)
Small and medium enterprises (SMEs) play a vital role in the Singapore and Malaysian economy and areconsidered to be the backbone of industrial development in the countries. This paper tries to investigate howgovernment play role in development of SMEs and in what kind of support. The key messages from this paperare SMEs in both countries were facing some similar problems especially from foreign competitors and accessto business opportunities but both had a different approach. In Malaysia, it is very clear that SMEs developmentis a part of efforts to restructure economic activities among ethnics groups. National Strategy for SMEdevelopment is also put in place. There is a synergic effort among government bodies to develop SMEs. BankNegara Malaysia plays an active role in supporting and financing. In Singapore, SMEs development programsare aimed as a conscious effort to foster local private enterprise. The strategy is applied to support theestablishment, development and then internationalization. Internationalization is stressed as Singapore openseconomy where free trade and globalization are as the soul. In the effort, no protection is given but support.Government strategy is to improve Money, Managerial, Market and Know-how it does. To increase access toglobal market, government assists SMEs in term of competency, connection and capital. Government requiresthe MNCs to serve both as mentors and as market outlets for their products. The target is to achieve theinternational competitiveness of SMEs through technology and international marketing requisites such asglobal standard and quality on the hope, SMEs will become a valuable partner in the future economic developmentof Singapore.